¹¹B and ⁷Li MAS NMR of glassy and crystalline borate compounds - Sergeev, N.A.; Padlyak, B.V.; Olszewski, M.; Stepien, P. (Functional Materials, 2014)
The MAS NMR spectra of the ¹¹B and ⁷Li isotopes in a series of un-doped crystalline and glassy borate compounds with Li₂B₄O₇, LiB₃O₅ and LiCaBO₃ chemical compositions were investigated and analyzed. The investigated borate glasses of high optical quality and chemical purity were obtained from corresponding polycrystalline compounds using standard glass synthesis technique. The obtained results of MAS NMR spectroscopy show good correlation with X-ray diffraction data for local structure of the cationic sites in borate crystals and glasses with same chemical compositions.